2019
DOI: 10.5713/ajas.18.0713
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the energy contents and nutrient digestibility of corn, waxy corn and steam-flaked corn fed to growing pigs

Abstract: Objective The research was conducted to determine the digestible (DE) and metabolizable energy (ME) contents as well as the apparent total tract digestibility (ATTD) of nutrients in corn, waxy corn and steam-flaked corn fed to growing pigs. Methods Eighteen growing pigs with initial body weight of 15.42±1.41 kg were randomly allotted to three diets including a corn diet, a waxy corn diet and a steam-flaked corn diet in a completely randomized design. Each treatment cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
2
2
3
Order By: Relevance
“…The average range of CP and EE in corn grain (7.61-8.44, 3.68-4.95) and cassava chips (1.51-2.27, 0.67-1.02) were similar to many previous studies that reported cassava chips and corn grain as high-starch energy source feeds, with cassava chips containing 2.3% CP and 0.3% EE and corn grain containing 8.8% CP and 4.7% EE (Suksombat et al, 2007). The reduction of CP and EE contents in all treated cassava chips and corn grain in this experiment were similar to the findings of Ma et al (2019), who found that, after steaming, the bulk density of normal corn grain and the CP and EE concentrations decreased. This occurred because a higher-temperature treatment at 100 °C reduced the CP and EE concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…The average range of CP and EE in corn grain (7.61-8.44, 3.68-4.95) and cassava chips (1.51-2.27, 0.67-1.02) were similar to many previous studies that reported cassava chips and corn grain as high-starch energy source feeds, with cassava chips containing 2.3% CP and 0.3% EE and corn grain containing 8.8% CP and 4.7% EE (Suksombat et al, 2007). The reduction of CP and EE contents in all treated cassava chips and corn grain in this experiment were similar to the findings of Ma et al (2019), who found that, after steaming, the bulk density of normal corn grain and the CP and EE concentrations decreased. This occurred because a higher-temperature treatment at 100 °C reduced the CP and EE concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…Ma et al (2019) reported that the mean energy values of dent corn and waxy corn varieties were 378.5 and 380.5 kcal 100 g -1 , respectively, which were slightly higher than the energy values calculated in this study. The difference is probably related to the higher oil and protein contents of waxy Corn genotypes used in the experiment compared to those used by [38]. The energy values, similar to the grain chemical composition, are under the influence of the genetic structure.…”
Section: Discussioncontrasting
confidence: 86%
“…The starch ratios of waxy corn genotypes have been reported between 69.01 and 73.2% [7,47,38]. The differences between starch ratios reported in the literature and those obtained in this study can be attributed the difference in the genotypes used.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations